MINIMALLY INVASIVE LUMBAR ARTHRODESIS AND PERCUTANEOUS PEDICLE SCREWS: A SYSTEMATIC REVIEW - BENITES,VINICIUS DE MELDAU (2020)
ABSTRACT A systematic review of the literature was performed in order to organize, evaluate, and select evidences available about the safety and efficacy of minimally invasive percutaneous arthrodesis with percutaneous pedicle screws in the treatment of patients with degenerative disc disease (and other spinal pathologies) as compared to conventional arthrodesis. PubMed, EMBASE and Cochrane Library databases were consulted to locate clinical trials and case reports/case series published in English between 2014 and 2019. After selection according to the inclusion/exclusion criteria, 21 of the 197 articles identified were chosen for a complete reading and used for the present review. Although the level of evidence of most of the studies included made the demonstration of efficacy and superiority among the surgical techniques reviewed difficult, the findings related to the minimally invasive procedure indicate a safe and reliable approach for the treatment of lumbar diseases. Level of evidence II; Systematic review of literature.